PONDOK KASEPUHAN ASSUNNIYAH KENCONG JEMBER SEBAGAI WADAH PEMBINAAN TAZKIYATUN NAFS BAGI SANTRI LANSIA (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2025)
Many elderly people experience anxiety about physical decline, the uncertainty of life and when the end of their lives will come, which is the background for Pondok Kasepuhan Assunniyyah to guide elderly people, with lessons about worship, guidance in reading the Koran, daily wirid, and mujahadah, to be able to obtain peace, to be able to reach out Khusnul Khatimah at the end of life. The aim of the research is to 1) determine the efforts of Pondok Kasepuhan Assunniyyah to become a forum for development tazkiyatun nafs for elderly students, 2) Mapping the curriculum tazkiyatun nafs for elderly students so they can deliver Khusnul Khatimah at the end of life. Descriptive qualitative research method, with this type of research case study. The research object of Pondok Kasepuhan Assunniyah Kencong Jember. Selection of informants using techniques purposive sampling totaling 6 research informants. Data analysis used the Miles and Huberman method starting from data collection, data reduction, data presentation and conclusions, data validity using triangulation techniques. The results of this research show, 1) Pondok Kasepuhan Assunniyyah has succeeded in becoming an effective forum for spiritual development of elderly students, living life with calm, confidence, and being able to get closer to Allah SWT. 2) Through theory tazkiyatun nafs help elderly students deepen their relationship with Allah, increase their deeds of worship, and achieve Khusnul Khotimah at the end of life. The novelty of this research is that currently Pondok Kasepuhan Assunniyyah still does not have a structured curriculum, it needs government support and Islamic religious education institutions to develop a curriculum, in accordance with theory habitus.